How to Tackle the Issue of Undesirable Educational Quality of Township Boarding Schools in China: The Relationship between the Input of School Resources and Academic Performance of Boarding Students - Qian, Jia (Best Evidence in Chinese Education, 2026)
Township boarding schools, as an integral part of rural compulsory education in China, play a vital role in optimizing the allocation of educational resources and promoting educational equity. Nevertheless, many students at these schools are facing the challenge of “boarding but without receiving quality education.” Based on data from a survey of 903 boarding students from 28 township junior secondary boarding schools in Hubei Province, the study empirically and systematically examines how school resources affect academic achievement of boarding students using hierarchical linear models and threshold regression models.